The influence of magmatic fluids and phase separation on B systematics in submarine hydrothermal vent fluids from back-arc basins. (1st July 2018) - Wilckens, Frederike K.; Reeves, Eoghan P.; Bach, Wolfgang; Meixner, Anette; Seewald, Jeffrey S.; Koschinsky, Andrea; Kasemann, Simone A.
Abstract: The composition of submarine hydrothermal vent fluids is affected by a variety of processes, such as interaction of heated seawater with rocks and sediments, addition of magmatic fluids, as well as phase separation and segregation. How these processes specifically affect the vent fluid composition is still poorly understood. In particular, the relative role of phase separation and magmatic degassing, which is common in arc/back-arc hydrothermal systems, is not well known. To provide new insights into these processes, we analysed B contents and isotope ratios in hydrothermal vent fluids and volcanic rocks from the Manus Basin, Papua New Guinea, and Nifonea volcano, New Hebrides back-arc. These fluids show a range of salinities, gas contents, acidities, and host rock compositions; many of them are influenced by phase separation and by addition of magmatic volatiles (both CO2 and SO2 ). Previous studies of hydrothermal vents in arc/back-arc settings suggest that B contents and isotopic composition of vent fluids are controlled by interactions between seawater, basement and sediments, and propose that phase separation and magmatic fluids play only a subordinate role. In our study, we demonstrate that vent fluids with minor magmatic input indeed reflect the interaction between seawater and oceanic crust. In contrast, the low-salinity Nifonea fluids and some of the acid-sulphate fluids from the Manus Basin have higher B contents as expected, whereas other volatile-rich fluids from the Manus Basin show B depletions. The lack of correlation between B contents and the intensity of magmatic fluid influx (CO2 and SO2 ) may indicate that magma degassing is not responsible for the B enrichments or depletions in these vent fluids. B enrichments might be related to preferential partitioning of B into the vapour phase during phase separation under PT-conditions well above the two-phase curve and critical line (i.e. T >> Tcritical, P >> Pcritical ). However, this cannot explain the low B concentrations in the vapour-rich vent fluids from the Manus Basin and the low B isotope ratios in the Nifonea fluids. Instead, we propose that B concentrations and isotope ratios in submarine vent fluids largely depend on the residence and reaction time of the vent fluid in the subsurface. In general, all vent fluids are still influenced by water-rock interaction during hydrothermal circulation. However, vent fluids with short residence times define a trend towards lower B concentrations and isotope ratios, which can be explained by mixing between hydrothermal and magmatic fluid, which is similar to the composition of the host rock. In contrast, the B signature of the magmatic fluid can be overprinted due to preferential mobilisation of B from the oceanic crust into vapour-rich fluids at longer reaction times. Thus, B may provide a tool for estimating the extent of B leaching and hence hydrothermal alteration in the subseafloor.